2015
DOI: 10.1016/j.bbrc.2015.09.094
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein protect pancreatic injury in rats with severe acute pancreatitis by inhibiting pro-inflammatory cytokines expression

Abstract: Baicalein demonstrated a well curative capability on rats with SAP. The mechanism may be alleviateing pancreatic injury and inhibiting pro-inflammatory cytokines expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Previous studied showed that baicalein, an active compound isolated from S. baicalensis Georgi, exert anti‐inflammatory, and anti‐tumor effects on CP and PDAC. Baicalein was shown to inhibit the inflammatory response of acinar cells and macrophages in vivo and in vitro (Li et al, ; Zhou et al, ). Here we report results from in vitro experiments aimed at characterizing the effects of baicalein on ADM in pancreatic acinar cells induced by rTNFα and macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studied showed that baicalein, an active compound isolated from S. baicalensis Georgi, exert anti‐inflammatory, and anti‐tumor effects on CP and PDAC. Baicalein was shown to inhibit the inflammatory response of acinar cells and macrophages in vivo and in vitro (Li et al, ; Zhou et al, ). Here we report results from in vitro experiments aimed at characterizing the effects of baicalein on ADM in pancreatic acinar cells induced by rTNFα and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein (5, 6, 7‐trihydroxy‐2‐phenyl‐4H‐1‐benzopyran‐4‐one), one of its derived product, is a flavonoid with a defined chemical structure, reported to possess excellent anti‐inflammatory, and anti‐tumor activities (Gao, Snyder, Smith, & Chen, ). Baicalein could alleviate experimental pancreatitis by inhibiting the expression of pancreatic enzyme and cytokines via multiple pathways (Li et al, , b). To the best of our knowledge, there are only a few previous reports on the effects of baicalein on pancreatic ADM mainly focused on its effect on apoptosis and proliferation (Cathcart et al, ; Chen et al, ; Guo et al, ; He et al, ; Lian et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory processes were not part of this study and we could not confirm an anti-inflammatory effect after s.c. injection of baicalein as it was shown after experimental traumatic brain injury [67]. Therefore, it is advisable to use an alternative route of administration, such as orally [50, 68] or intravenously [69]. …”
Section: Discussionmentioning
confidence: 99%
“…However, excessive inflammatory reactions result in severe acute pancreatitis (SAP), with a high mortality and morbidity [13]. Although the pathogenesis of SAP has not yet been clarified, inflammatory mediators such as IL-1 β , IL-6, IL-8, IL-10, tumor necrosis factor-alpha (TNF)- α , platelet-activating factor, and monocyte chemotactic protein-1 (MCP-1) are considered vital for SAP development [38]. In vitro, glibenclamide significantly reduced IL-1 β release in lipopolysaccharide- (LPS-) induced peritoneal cells [13].…”
Section: Anti-inflammatory Roles Of Glibenclamidementioning
confidence: 99%